The politics of repressing environmentalists as agents of foreign influence. Issue 2 (4th March 2018) - Matejova, Miriam; Parker, Stefan; Dauvergne, Peter
ABSTRACT: Theoretically, this article reveals the long-term risk for local non-governmental organisations (NGOs) of participating in transnational advocacy networks (TANs), accepting money from foreign sources and throwing 'boomerangs' internationally—a strategy used by local NGOs to seek international allies to pressure repressive and unresponsive states at home. Focusing primarily on the suppression of environmental NGOs that oppose natural-resource extraction, this article examines three cases—Russia, India and Australia—to illuminate the consequences of this trend for local civil society and TANs. It also documents a global trend towards states depicting local NGOs with international linkages as subversive agents of foreign interests, justifying legal crackdowns and the severing of foreign funding and ties. State framing of NGOs as agents of foreign interests is repressing local environmental activism, depoliticising civil society and weakening international NGO alliances—a conclusion with far-reaching consequences for the future of TANs, local NGOs and environmental activism.